Arsenic exposure levels in relation to different working departments in a copper mining and smelting plant. (October 2015) - Sun, Qingshan; Song, Yingli; Liu, Shengnan; Wang, Fei; Zhang, Lin; Xi, Shuhua; Sun, Guifan
Abstract: The investigation was carried out to evaluate arsenic exposure and the urine metabolite profiles of workers with different working departments, including administration (Group1), copper ore mining (Group2), copper ore grinding (Group3), electrolytic procession (Group4) and copper smelting (Group5) in a Copper mining and processing plant in China. Information about characteristics of each subject was obtained by questionnaire and inorganic arsenic (iAs), monomethylarsonic acid (MMA), dimethylarsinic acid (DMA) in urine were determined. The highest urinary levels of iAs, MMA and DMA all were found in the Group 5. Group 4 workers had a higher iAs% and a lower PMI compared to Group 3. The urinary total As (TAs) levels of 54.7% subjects exceeded 50 μg/g Cr, and the highest percentage (93.3%) was found in Group 5, smelters. The results of the present study indicate that workers in copper production plant indeed exposed to As, especially for smelters and workers of electrolytic process. Highlights: The highest urinary levels of iAs, MMA and DMA all were found in copper smelters. Workers engaged in electrolytic procession had higher urinary iAs% and lower PMI. Different working departments increased the risk of TAs exceeded BEI after adjusting confounders. Seafood and years of employment may influence SMI.